The Benefits of Multimodality in EFL Reading Learning Instructions - Kristian Florensio Wijaya (Journal of English Language and Pedagogy (JELPA), 2026)
In modern literacy enterprises, process-oriented pedagogical approaches are considered essential elements in guiding learning participants to remain purposeful towards their previously determined objectives. A similar trajectory goes with the meaningful conveyance of reading-learning instructions, where second language educators should actualize supportive, constructive, and comprehensive means of knowledge discovery dynamics. In line with this objective, the researcher conducted this qualitative library study to explore the benefits of multimodality in EFL reading instruction. To do so, the researcher employed a thematic analysis approach in analyzing 30 previously published studies that were harmonious with the main subject-specific matter forming the basis of this investigation. A thematic analysis method was applied due to its usefulness in yielding more reliable, robust, and contextualized findings that contribute to the advancement of specific discipline fields. From the thematically subsumed research results, the internalization of multimodality significantly enhanced the clarity of reading-learning instructions. This is indicated by the promising development of EFL learners’ reading proficiency and motivation.